2010
DOI: 10.1155/2010/928097
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Impact of a “Health-at-Every-Size” Intervention on Weight-Preoccupied Overweight/Obese Women

Abstract: The aim of the present study was to assess the impact of a “Health-at-every-size” (HAES) intervention on psychological variables and body weight the weight-preoccupied overweight/obese women. Those women were randomized into three groups (1) HAES, (2) social support (SS), (3) waiting-list (WL), and were tested at baseline, post-treatment and six-month and one-year follow-ups. All participants presented significant psychological improvement no matter if they received the HAES intervention or not. However, even … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(76 citation statements)
references
References 40 publications
(72 reference statements)
1
68
0
7
Order By: Relevance
“…Crerand et al (27) , for example, found that the 'dieting' group, which included those following either a meal replacement diet or a balanced deficit diet, scored significantly better on the depression index compared with the IE group at 40 weeks post-treatment. In the longer term, however, the IE participants continued to show improvements whereas others regressed (26,29) . Crerand et al (27) hypothesised that the increases in psychological health among the dieting group were most likely due to weight loss, which would most likely be regained over time, whereas those among the non-diet group were likely due to attitudinal shifts, which are likely to last longer.…”
Section: Intuitive Eating and Physical Health Indicators Other Than Bmimentioning
confidence: 87%
See 3 more Smart Citations
“…Crerand et al (27) , for example, found that the 'dieting' group, which included those following either a meal replacement diet or a balanced deficit diet, scored significantly better on the depression index compared with the IE group at 40 weeks post-treatment. In the longer term, however, the IE participants continued to show improvements whereas others regressed (26,29) . Crerand et al (27) hypothesised that the increases in psychological health among the dieting group were most likely due to weight loss, which would most likely be regained over time, whereas those among the non-diet group were likely due to attitudinal shifts, which are likely to last longer.…”
Section: Intuitive Eating and Physical Health Indicators Other Than Bmimentioning
confidence: 87%
“…These latter approaches, however, generally argue that one can be healthy regardless of (over)weight and often address prejudice against overweight or obese people (26)(27)(28)(29) . Intuitive eating, in contrast, usually omits discussion of body weight or whether attaining a 'normal' weight is one of its goals.…”
Section: Development and Validity Of Scales To Measure Intuitive Eatingmentioning
confidence: 99%
See 2 more Smart Citations
“…Some fat acceptance interventions, notably size acceptance interventions such as those based on the Health at Every Size movement, have shown to improve health even in the absence of weight loss, and are therefore a promising tool (Bacon, 2010;Bacon, Stern, Van Loan, & Keim, 2005;Carroll, Borkoles, & Polman, 2007;Provencher et al, 2009). Similar interventions have also yielded positive weight (Anglin, 2012;Gagnon-Girouard et al, 2010;Lillis, Hayes, Bunting, & Masuda, 2009;Rapoport, Clark, & Wardle, 2000;Tanco, Linden, & Earle, 1998), fitness (Carrier, Steinhardt, & Bowman, 1994) and psychological outcomes (Ciliska, 1998;Gagnon-Girouard et al, 2010;Lillis et al, 2009;Omichinksi & Harrison, 1995;Tanco et al, 1998). However, some interventions that target weight stigma have found no significant benefits, such as one that targeted internalized weight bias, which found no benefit over an environmental modification and habit formation disruption intervention (Carels et al, 2014), and some longitudinal studies found that higher weight stigma is associated with better weight loss outcomes (e.g., Latner, Wilson, Jackson, & Stunkard, 2009).…”
Section: Model Summary and Future Researchmentioning
confidence: 99%